A tertiary hospital audit of the use of medical imaging in the 24 h preceding death. Issue 2 (February 2016) - Liu, D.; Weil, J.; Boughey, M.; Sutherland, T.
Abstract : This study aims to investigate the number, modality and indication for imaging studies performed on acute hospital inpatients in the 24 h prior to death. Data were obtained from retrospective analysis of deceased patients from a university affiliated tertiary hospital over a 2‐year period and it was found that around one in five inpatients received medical imaging in the last 24 h of their life (364 of 1855, 19.6%).